2012
DOI: 10.1118/1.4709601
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a virtual source model for Monte Carlo dose calculations of a flattening filter free linac

Abstract: The virtual source model for flattened beams was successfully adapted to a flattening filter free beam production. Water phantom and patient specific QA measurements show excellent results, and comparisons of IMRT plans generated in conventional and FFF mode are underway to assess dosimetric uncertainties and possible improvements in dose calculation and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…Removing the filter results in a highly forward‐peaked beam profile, increases the dose rate, and softens the beam. While several recent papers have summarized the dosimetric characteristics of these beams 1 , 2 , 3 and others have reported commissioning results of the anisotropic analytical algorithm (4) or Monte Carlo, 5 , 6 , 7 scarce data exist on modeling these beams with the collapsed cone convolution superposition (CCCS) algorithm as implemented in the widely used Pinnacle 3 treatment planning system (Philips Radiation Oncology Systems, Fitchburg, WI). Stathakis et al (8) reported their experience commissioning the CCCS algorithm for 6 and 18 MV unflattened beams by overriding interlocks related to the flattening filter, but no patients were treated with this configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Removing the filter results in a highly forward‐peaked beam profile, increases the dose rate, and softens the beam. While several recent papers have summarized the dosimetric characteristics of these beams 1 , 2 , 3 and others have reported commissioning results of the anisotropic analytical algorithm (4) or Monte Carlo, 5 , 6 , 7 scarce data exist on modeling these beams with the collapsed cone convolution superposition (CCCS) algorithm as implemented in the widely used Pinnacle 3 treatment planning system (Philips Radiation Oncology Systems, Fitchburg, WI). Stathakis et al (8) reported their experience commissioning the CCCS algorithm for 6 and 18 MV unflattened beams by overriding interlocks related to the flattening filter, but no patients were treated with this configuration.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4b and c, the off-axis profiles have convex distributions that agree with the literature. [310131516181920] The profile in the off-axis direction at the 0.7-cm depth, where many contamination electrons are contained, differs from the profiles at deeper positions under the influence of entrained electrons. This is because the electron beam spreads laterally after entering water and is larger than X-rays, as shown in Figure 4a.…”
Section: Resultsmentioning
confidence: 99%
“…The dose distribution for FFF linacs determined using Monte Carlo (MC) simulations,[34567891011] as well as measured data from treatment apparatuses in clinical use,[89101112131415161718] has been published. Most of such experimental studies employed commercial linacs with a metal plate, such as copper or aluminum, inserted to absorb the primary and secondary electrons created in materials in the linac head.…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible solutions is to ignore all the details of the hardware and adopt a source model based on the parameters obtained by fitting the energy spectrum, the radial, and angular distributions with analytical functions to measured data. We may refer this kind of method to as a virtual analytical source model (VASM) . In this work, we developed an alternative approach, for which we call a virtual machine source model (VMSM) to distinguish it from a VASM.…”
Section: Introductionmentioning
confidence: 99%